Remarks at the Fourth Ministerial of the Coalition of Finance Ministers for Climate Action - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank, spoke about the Coronavirus (COVID-19) pandemic that has underscored the deep connections between economic systems, human health, and global well-being. Ccountries now have a chance to set themselves on a greener, smarter, and more equitable development path. It is critical that countries work toward their climate and environmental goals. As countries find themselves saddled with rising debt, there is also an opportunity now to reform harmful subsidies from agriculture and fisheries to fossil fuels. Subsidy reform can provide a triple dividend by making the economic recovery fiscally sound, environmentally sustainable, and resilient to future shocks. The World Bank Group remains the largest multilateral funder of climate investments in developing countries. The World Bank Group helps countries put an economic value on biodiversity including forests, land, and water resources so they can better manage these natural assets.